Forage production from tallgrass prairie burned annually in autumn, winter, or spring - E.G. Towne (Kansas Agricultural Experiment Station Research Reports, 2003)
Aboveground biomass production was measured on upland and lowland prairie in replicated, ungrazed watersheds at the Konza Prairie Biological Station (Manhattan, KS) that were burned annually for seven years in either autumn (November), winter (February), or spring (April). Average grass and forb biomass did not significantly differ among burn seasons on either topographic site, although production fluctuated considerably over years. Results of this study contrast with many of the conventional views of how tallgrass prairie vegetation responds to seasonal fire.
Keywords: Cattlemen& #x27; s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Forage production; Biomass production; Tallgrass prairie; Burning